Ultrasound Guided Suprascapular Nerve Block versus Intra-articular Steroid Injection in the Treatment of Periarthritis Shoulder: A Randomised Clinical Trial - Sakshi Jain (JCDR Research and Publications Private Limited, 2021)
Introduction: Suprascapular Nerve Block (SSNB) and Intra-articular (IA) steroid injection are used for management of Periarthritis (PA) of shoulder with variable results. Aim: To compare the efficacy of SSNB and IA steroid injection for management of PA shoulder. Materials and Methods: In this randomised clinical trial, 100 patients of PA shoulder from Physical Medicine and Rehabilitation (PMR) Outpatient Department (OPD) were enrolled over the period of 18 months and were divided in two equal groups using computerised block randomisation. Group A patients received IA methylprednisolone while Group B patients were subjected to Ultrasound (USG) guided SSNB. Assessment was done at baseline and at 1, 4 and 12 weeks after the intervention, using Numerical Pain Rating Scale (NPRS), active and passive Range Of Motion (ROM) of shoulder and Shoulder Pain And Disability Index (SPADI). Statistical significance was determined by Chisquare for qualitative variables and by unpaired t-test or paired t-test for quantitative variables. The p<0.05 was taken as a level of statistical significance. Results: Both groups had significant improvement (p<0.0005) in pain, ROM and functional index at all follow-ups. Comparison between the groups revealed a better outcome in Group A, in terms of NPRS, SPADI score, internal and external rotations at 1, 4 and 12 weeks (p<0.0005). Both the groups were comparable in terms of abduction, flexion and extension at first week (p<0.0005) with Group A showing better improvement at subsequent follow-up. Conclusion: Both SSNB and IA steroid injection can be used for treatment of PA shoulder but IA steroid injections gave better results as compared to SSNB. SSNB may be used as an adjunct to exercise therapy and as an alternative to IA steroid injection if required.